2017
DOI: 10.1002/app.45752
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of extremely biocompatible double‐network hydrogels based on chitosan and poly(vinyl alcohol) with enhanced mechanical properties

Abstract: An easy and ecofriendly method for designing double‐network (DN) hydrogels based on chitosan and poly(vinyl alcohol) (PVA) with high mechanical performance is described. When covalent bonds in the networks are used as crosslinking agents in the achievement of a higher mechanical strength, the irreversible deformation of these hydrogels after a large force is applied is still one of the most important obstacles. To overcome this problem, we used physical crosslinking for both networks. The mechanical strength, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Double network (DN) hydrogels comprising two interpenetrating and cross-linked polymer networks have gained tremendous attention due to their enhanced mechanical property. Many investigations have reported that DN hydrogels exhibited improved mechanical properties and high adsorption capacities for heavy metals and dyes [12,13,14]. For example, a SA/polyvinyl alcohol (PVA) DN hydrogel was prepared for the purpose of achieving enhanced mechanical properties and electrical conductivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Double network (DN) hydrogels comprising two interpenetrating and cross-linked polymer networks have gained tremendous attention due to their enhanced mechanical property. Many investigations have reported that DN hydrogels exhibited improved mechanical properties and high adsorption capacities for heavy metals and dyes [12,13,14]. For example, a SA/polyvinyl alcohol (PVA) DN hydrogel was prepared for the purpose of achieving enhanced mechanical properties and electrical conductivity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanistic pathways for either assay are not entirely understood, it is thought that the resazurin is reduced either in chemically reduced media produced by cellular growth or enzymatic reduction within the mitochondria, while MTT reduction is likely to occur exclusively intracellularly by mitochondrial enzymes. , The resazurin assay (first discussed in 1977) represents a unique alternative to the popular MTT assay, as it is nontoxic to cells and can be used for extended incubation or growth experiments, while the MTT assay (originally cited by Mosmann in 1983) is generally thought to be more sensitive in its ability to detect small changes within a viable cell population. Both assays were tested for interferences in this study due to their prevalence in the field of determining cytotoxicity or cell viability in the presence of novel therapeutic agents. …”
Section: Resultsmentioning
confidence: 99%
“…This may be due to its relatively poor tensile strength. At a tensile strength of 0.128 MPa, Hussain et al [ 88 ] found their glycogen-derived hydrogel to have an average value amongst the group, and certainly inferior to other biopolymer-derived hydrogels like chitosan and gelatine, as collated in a review by Hua et al [ 88 , 89 , 90 , 91 ]. However, the glycogen-derived hydrogel demonstrated superior elongation at fracture, reaching 810% strain.…”
Section: The History Contemporary Status and Future Applicationsmentioning
confidence: 99%